2006
DOI: 10.1353/csd.2006.0030
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Student Mental Health: Needs Assessment and Utilization of Counseling Services

Abstract: This study examined the mental health needs, knowledge, and utilization of counseling services among graduate students at a large university in the western United States. Almost half of graduate student respondents reported having had an emotional or stress-related problem over the past year, and over half reported knowing a colleague who had had an emotional or stress-related problem over the past year. Self-reported mental health needs were significantly and negatively related to confidence about one s finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
290
1
18

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(331 citation statements)
references
References 33 publications
9
290
1
18
Order By: Relevance
“…In doctoral programmes, higher level of stress was reported by women than men (Oswalt & Riddock, 2007;Toews et al, 1997). One reason cited for more levels of stress among women was that these female graduate students have added the role of student to an already existing set of care taking and other life roles (Hyun, Quinn, Madon & Lusting, 2006;Stratton, Mielke, Kirshenbaum, Goodrich & McRae, 2006). Similarly, Smith, Maroney, Nelson, Lable and Abel (2006) stated that graduate students have many concerns such as finances, children, aging parents, community responsibilities, and partner relationships.…”
Section: Challenges In the Doctoral Journeymentioning
confidence: 99%
See 1 more Smart Citation
“…In doctoral programmes, higher level of stress was reported by women than men (Oswalt & Riddock, 2007;Toews et al, 1997). One reason cited for more levels of stress among women was that these female graduate students have added the role of student to an already existing set of care taking and other life roles (Hyun, Quinn, Madon & Lusting, 2006;Stratton, Mielke, Kirshenbaum, Goodrich & McRae, 2006). Similarly, Smith, Maroney, Nelson, Lable and Abel (2006) stated that graduate students have many concerns such as finances, children, aging parents, community responsibilities, and partner relationships.…”
Section: Challenges In the Doctoral Journeymentioning
confidence: 99%
“…These are just some examples of the many ways today's graduate students are impacted by economical and societal discourses. These manifold and overlapping responsibilities can impact female students' emotional well-being and the likelihood of completing their program of study (Hyun et al, 2006). Due to the various roles women have to assume in their daily life, balancing personal and professional development becomes a serious challenge, which in turn leaves them to experience inter-role conflict between their personal and academic roles (Johnson, Batia & Haun, 2008;Offstein, Larson, McNeill & Mjoni, 2004;Raddon, 2002).…”
mentioning
confidence: 99%
“…In fact, some have found a higher correlation between academic problems and sleep than alcohol use, stress, depression, colds or flu (Prichard, Cunningham & Broek, 2013). Likewise, it is well documented that stress and other mental health issues pose challenges for and are increasing among college students (Eisenberg, Gollust, Golberstein, & Hefner, 2007;Gallagher, 2011;Hyun, Quinn, Madon, & Lustig, 2006). Such mental health concerns may impede sleep patterns; for example, Wyatt and Oswalt (2013) found that among a nationally representative sample of college students, approximately 25% of undergraduate students and 20% of graduate students identified sleep difficulties as a major concern within the last 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…On a lighter note, the sheer number of blogs and comic strips discussing or satirizing the PhD experience (such as http://xkcd.com/ , http://phdcomics.com/ , and http://whatshouldwecallgradschool.tumblr.com/ ) highlight the confusion, loneliness, and emotional toil encountered by emerging researchers. Meanwhile, there is relatively sparse research on the emotional well-being of graduate students (Hyun, Quinn, Madon, & Lustig, 2006).…”
Section: Graduate School and The Transition From Student To Researchermentioning
confidence: 99%